Given that f(x)= x^3/4 +6
a) Find f(4)
b) Find f^-1(x)
c) Find f^-1(8)
![Given that fx x34 6 a Find f4 b Find f1x c Find f18 class=](https://us-static.z-dn.net/files/d7a/3e17f2c406b34a280091d11caf64d717.png)
a)
[tex]f(4)=\dfrac{4^3}{4}+6=4^2+6=16+6=22[/tex]
b)
[tex]\begin{aligned}\\&y=\dfrac{x^3}{4}+6\\&4y=x^3+24\\&x^3=4y-24\\&x=\sqrt[3]{4y-24}\\&f^{-1}(x)=\sqrt[3]{4x-24}\end[/tex]
c)
[tex]f^{-1}(8)=\sqrt[3]{4\cdot8-24}=\sqrt[3]{8}=2[/tex]
Answer:
[tex]\displaystyle \large{f(4)=22}\\\\\displaystyle \large{f^{-1}(x)=\sqrt[3]{4x-24}}\\\\\displaystyle \large{f^{-1}(8) = 2}[/tex]
Step-by-step explanation:
In this problem, we are given the linear function:
[tex]\displaystyle \large{f(x)=\dfrac{x^3}{4}+6}[/tex]
( a ) Find f(4)
Simply substitute x = 4 in the function f(x).
[tex]\displaystyle \large{f(4)=\dfrac{4^3}{4}+6}\\\\\displaystyle \large{f(4)=4^2+6}\\\\\displaystyle \large{f(4)=16+6}\\\\\displaystyle \large{f(4)=22}[/tex]
( b ) Find the inverse
To find [tex]\displaystyle \large{f^{-1}(x)}[/tex], solve for x-term then swap x-term and y-term.
[tex]\displaystyle \large{4f(x)=x^3+24}\\\\\displaystyle \large{4f(x)-24=x^3}\\\\\displaystyle \large{\sqrt[3]{4f(x)-24}=\sqrt[3]{x^3}}\\\\\displaystyle \large{x=\sqrt[3]{4f(x)-24}}[/tex]
Swap f(x) and x.
[tex]\displaystyle \large{f^{-1}(x)=\sqrt[3]{4x-24}}[/tex]
( c ) Find inverse f(8)
Substitute x = 8 in inverse function.
[tex]\displaystyle \large{f^{-1}(8) = \sqrt[3]{4(8)-24}}\\\\\displaystyle \large{f^{-1}(8) = \sqrt[3]{32-24}}\\\\\displaystyle \large{f^{-1}(8) = \sqrt[3]{8}}\\\\\displaystyle \large{f^{-1}(8) = 2}[/tex]
Please let me know if you have any doubts!